DESAIN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS VIDEO KEARIFAN LOKAL MATERI POLA BILANGAN ERA 5.0 - Venissa Dian Mawarsari; Winda Kustriani; Iswahyudi Joko (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Teachers often face challenges in creating effective learning materials, particularly in mathematics. Traditional lecture methods and insufficiently engaging learning tools can lead to student disinterest. Hence, it is essential to develop mathematics learning media that stimulate interest and connect to real-world experiences, including local cultural practices. Therefore, this study aimed to design effective learning media for Year 8 students focused on number patterns and to assess the validity of this media. This research adopted a development approach, utilizing the Analysis, Design, and Development (ADDIE) method. The development process was limited to the Analysis, Design, and Development stages. An assessment questionnaire was used to evaluate the validity of the video media, with input from both media experts and material experts. Five experts from each field were consulted for media validation. Results of the validation process indicated that the video media scored 88% and 87% in the material expert and media expert evaluations, respectively. These scores met the criteria for validity, indicating that the media is suitable for use in the classroom.